Assessment of the ability of the Privigen® purification process to deplete thrombogenic factor XIa from plasma. Issue 1 (13th December 2013) - Komenda, M.; Stadler, D.; Malinas, T.; Moses, M.; Pragst, I.; Herzog, E.; Schmutz, P.; Minnig, K.; El Menyawi, I.
<x xml:space="preserve">Abstract</x> Background and objectives Activated clotting factor FXI (FXIa) has been postulated to play a significant role in thromboembolic events potentially associated with the administration of intravenous immunoglobulin. The purpose of this study was to demonstrate that thrombogenic agents, in particular FXIa and FXI, are depleted or inactivated in Privigen®. Materials and methods The ability of the purification process to deplete FXIa from plasma was studied. All steps of the Privigen® production were investigated for potential activation of FXI to FXIa with spiking experiments. Results Privigen® contains no procoagulant activity as determined by FXIa chromogenic assay, non‐activated partial thromboplastin time (NaPTT) and thrombin generation assays (TGA, FXIa‐like activity). The coagulation times were >200 s in the NaPTT test. FXIa was below the detection limit of 0·14 ng/ml (chromogenic assay) and below the quantification limit of 0·2 ng/ml (TGA). FXIa spiking experiments showed that the analytical methods used can detect traces of procoagulant activity in immunoglobulin samples. FXIa spiking and kinetic experiments during the octanoic acid fractionation step showed that a substantial reduction in FXIa specific activity (by ≥99·9% within 40 min of octanoic acid incubation) was reached already at an early stage of the manufacturing process. These results were confirmed in vivo: in a modified Wessler test, no thrombus was reported. Conclusion The Privigen® manufacturing process has the capability to remove thrombogenic factors: octanoic acid precipitation, designed to remove a variety of contaminants during immunoglobulin purification, also removes almost all FXIa from plasma and further purification steps do not activate FXI.